Thermoregulated Coacervation, Metal-Encapsulation and Nanoparticle Synthesis in Novel Triazine Dendrimers - Fermín Ramírez-Crescencio; Alan E. Enciso; Mirza Hasan; Viviana C. P. da Costa; Onofrio Annunziata; Rocío Redón; Jeffery L. Coffer; Eric E. Simanek (Molecules, 2016)
The synthesis and solubility behaviors of four generation five (G5) triazine dendrimers are studied. While the underivatized cationic dendrimer is soluble in water, the acetylated and propanoylated derivatives undergo coacervation in water upon increasing temperature. Occurring around room temperature, this behavior is related to a liquid-liquid phase transition with a lower critical solution temperature (LCST) and is explained by differences in composition, notably, the hydrophobic nature of the terminal groups. Interestingly, the water solubility of the acetylated dendrimer is affected by the addition of selected metal ions. Titrating solutions of acetylated dendrimer at temperatures below the LCST with gold or palladium ions promoted precipitation, but platinum, iridium, and copper did not. Gold nanoparticles having diameters of 2.5 ± 0.8 nm can be obtained from solutions of the acetylated dendrimer at concentrations of gold less than that required to induce precipitation by treating the solution with sodium borohydride.